Automatic Vagus Nerve Stimulation Triggered by Ictal Tachycardia: Clinical Outcomes and Device Performance—The U.S. E‐37 Trial. Issue 2 (13th December 2015) - Fisher, Robert S.; Afra, Pegah; Macken, Micheal; Minecan, Daniela N.; Bagić, Anto; Benbadis, Selim R.; Helmers, Sandra L.; Sinha, Saurabh R.; Slater, Jeremy; Treiman, David; Begnaud, Jason; Raman, Pradheep; et al.
Abstract : Objectives: The Automatic Stimulation Mode (AutoStim) feature of the Model 106 Vagus Nerve Stimulation (VNS) Therapy System stimulates the left vagus nerve on detecting tachycardia. This study evaluates performance, safety of the AutoStim feature during a 3‐5‐day Epilepsy Monitoring Unit (EMU) stay and long‐ term clinical outcomes of the device stimulating in all modes. Materials and Methods: The E‐37 protocol (NCT01846741) was a prospective, unblinded, U.S. multisite study of the AspireSR ® in subjects with drug‐resistant partial onset seizures and history of ictal tachycardia. VNS Normal and Magnet Modes stimulation were present at all times except during the EMU stay. Outpatient visits at 3, 6, and 12 months tracked seizure frequency, severity, quality of life, and adverse events. Results: Twenty implanted subjects (ages 21–69) experienced 89 seizures in the EMU. 28/38 (73.7%) of complex partial and secondarily generalized seizures exhibited ≥20% increase in heart rate change. 31/89 (34.8%) of seizures were treated by Automatic Stimulation on detection; 19/31 (61.3%) seizures ended during the stimulation with a median time from stimulation onset to seizure end of 35 sec. Mean duty cycle at six‐months increased from 11% to 16%. At 12 months, quality of life and seizure severity scores improved, and responder rate was 50%. Common adverse events were dysphonia ( n = 7), convulsion ( n = 6), and oropharyngeal pain ( n = 3). Conclusions: The Model 106 performed as intended in the study population, was well tolerated and associated with clinical improvement from baseline. The study design did not allow determination of which factors were responsible for improvements.